Muscle Oxygenation, Neural, and Cardiovascular Responses to Isometric and Workload-matched Dynamic Resistance Exercise - Kounoupis, Anastasios; Dipla, Konstantina; Tsabalakis, Ioannis; Papadopoulos, Stavros; Galanis, Nikiforos; Boutou, Afroditi K.; Vrabas, Ioannis S.; Smilios, Ilias; Zafeiridis, Andreas (International Journal of Sports Medicine, 2021)
Differences in blood flow patterns and energy cost between isometric and dynamic resistance exercise may result to variant cardiovascular, neural, and muscle metabolic responses. We aimed to compare the cardiovascular, baroreceptor sensitivity, and muscle oxygenation responses between workload-matched, large muscle-mass isometric and dynamic resistance exercises. Twenty-four young men performed an isometric and a dynamic double leg-press protocol (4 sets×2 min) with similar tension time index (workload). Beat-by-beat hemodynamics, baroreceptor sensitivity, muscle oxygenation, and blood lactate were assessed. The increase in blood pressure was greater (p<0.05) in the 1st set during dynamic than isometric exercise (by ~4.5 mmHg), not different in the 2nd and 3rd sets, and greater in the 4th set during isometric exercise (by ~5 mmHg). Dynamic resistance exercise evoked a greater increase in heart rate, stroke volume, cardiac output, and contractility index (p<0.05), and a greater decline in peripheral resistance, baroreceptor sensitivity, and cardiac function indices than isometric exercise (p<0.05). Participants exhibited a greater reduction in muscle oxyhemoglobin and a greater increase in muscle deoxyhemoglobin in dynamic versus isometric exercise (p<0.001–0.05), with no differences in total hemoglobin and blood lactate. In conclusion, large muscle-mass, multiple-set isometric exercise elicits a relatively similar blood pressure but blunted cardiovascular and baroreceptor sensitivity responses compared to workload-matched dynamic resistance exercise. Differences in blood pressure responses between protocols appear small (~5 mmHg) and are affected by the number of sets. The muscle oxidative stimulus is greater during dynamic resistance exercise than workload-matched isometric exercise.
Keywords: muscle oxygenation; cardiac output; resistance exercise; static exercise; blood pressure; baroreceptor sensitivity